2016
DOI: 10.1002/jmv.24469
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of HCV among Cairo University students in Egypt

Abstract: Hepatitis C virus (HCV) is highly prevalent in Egypt. This work aimed at determining the seroprevalence of HCV among Cairo University students. The present study included 3,000 students from Cairo University, Egypt. Blood sample was obtained from each participant to be tested for HCV seromarker. HCV RNA detection by polymerase chain reaction (PCR) was carried out for those with positive anti-HCV. Overall prevalence rate of HCV antibody (anti-HCV) was 4.6%. It showed that the prevalence was relatively higher am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
7
4
Order By: Relevance
“…However, our HCV-RNA prevalence among the 498 anti-HCV positive subjects (71.3%) is higher than that detected by Nafeh et al 28 as well as Esmat et al 25 who documented HCV RNA in 62.8% and 31.4% of the anti-HCV-positive subjects, respectively. This difference between anti-HCV and HCV RNA positivity is mainly explained by the spontaneous viral clearance through innate immunity response in acute HCV infections.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…However, our HCV-RNA prevalence among the 498 anti-HCV positive subjects (71.3%) is higher than that detected by Nafeh et al 28 as well as Esmat et al 25 who documented HCV RNA in 62.8% and 31.4% of the anti-HCV-positive subjects, respectively. This difference between anti-HCV and HCV RNA positivity is mainly explained by the spontaneous viral clearance through innate immunity response in acute HCV infections.…”
Section: Discussioncontrasting
confidence: 71%
“… 24 Concerning our studied age group (15–19 years), our rates are definitely lower than that detected by EDHS 2008 (4.1%) 7 and Esmat et al report that there is 4.6% seroprevalence of anti-HCV among a comparably similar age group to our participants. 25 Our reported HCV prevalence is even lower than that reported for the least affected age group (1–9 years age). A previous study found that asymptomatic HCV infection in this pediatric age group is 2.02%.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Egypt is considered to have one of the highest prevalence rate of HCV, worldwide; with~14.7% of anti-HCV antibodies and 10% of chronic HCV infection. 2 It was reported that the incidence of HCV among Egyptians was around seven for every 1000 person/y corresponding to 500 000 infections every year. 3 Major HCV genotypes constitute genotype 1 to 6, while more than 50 subtypes are regarded, that have their specific patterns of geographical distribution.…”
Section: Funding Informationmentioning
confidence: 99%